A mixed method approach to describe the out‐of‐pocket expenses incurred by families of children with cancer1. Issue 3 (26th September 2012) - Tsimicalis, Argerie; Stevens, Bonnie; Ungar, Wendy J.; McKeever, Patricia; Greenberg, Mark; Agha, Mohammad; Guerriere, Denise; Naqvi, Ahmed; Barr, Ronald
Abstract Background Families of children with cancer are confronted with a broad range of direct costs (out‐of‐pocket expenses), but the nature of these costs is poorly understood. This study aimed to disaggregate and describe these costs. Procedure A prospective, mixed method, cost‐of‐illness design was utilized. Starting in the fourth week following their child's diagnosis, parents recorded resources consumed, and costs incurred for 1 week per month for 3 consecutive months. Any additional costs not captured in this typical 1 week period were added for the remainder of the month. Parents also discussed their costs in an audio‐taped interview at the end of the 3 months. Descriptive statistics and qualitative content analyses were performed to disaggregate and describe families' costs. Results In total, 99 families reported utilizing 16 cost categories and 74 cost items. Nearly three quarters of these costs were attributed to travel (56%) and food (18%). Costly items included acquisition of a car ($CAD35, 000), relocation of a family ($CAD6, 000), and purchase of a wheelchair ($CAD6, 800). Parents described facing significant out‐of‐pocket expenses to ensure that their children had access to cancer treatment, to cope with the clinical treatment side effects of treatment, and to maintain the family household. Conclusion Families of children with cancer experience a wide range of costs. Our understanding of the nature of their costs and resource use may formulate the basis for future cost assessments and provide insight into practice and policy changes aimed at lessening the economic impact of this burden. Pediatr Blood Cancer 2013; 60: 438–445. © 2012 Wiley Periodicals, Inc.